The Role of E-Commerce Through the Internet in the Era of Globalization Related to Trade Contracts and Transactions in Commerce in Society - Elyani; Dahris Siregar; Bobby Alhabsyi; Rio Apriyanto; Rahmad Kurniawan; Sari Devi; Siti Maharrani (IJCS: International Journal of Community Service, 2022)
In this era of globalization, the development of science and technology has been increasing rapidly. The discovery of the internet which is an information technology capable of helping people in exchanging information with anyone. Over time, the growing globalization in information technology also has an impact on electronic commerce (e-commerce) and the occurrence of trade contracts. Trade contracts or agreements are made by the parties through an electronic system, meaning that the parties do not meet face to face. The concept of e-commerce certainly provides advantages or advantages in its use when compared to conventional concepts. Some of the advantages or advantages of e-commerce are that information can be obtained in more detail, quickly without any time limits, including places and the transaction process is much easier to do. This study uses a descriptive method with a normative approach to obtain data. The collected data will be analyzed using qualitative analysis, which is described in sentences. The purpose of this research is to find out the role of e-commerce in the era of globalization and how people use or take advantage of e-commerce .